Functions of nitric oxide-mediated post-translational modifications under abiotic stress - Mata-Pérez, Capilla; Sánchez-Vicente, Inmaculada; Arteaga, Noelia; Gómez-Jiménez, Sara; Fuentes-Terrón, Andrea; Oulebsir, Cylia Salima; Calvo-Polanco, Mónica; Oliver, Cecilia; Lorenzo, Óscar (Frontiers in Plant Science, 2023)
Environmental conditions greatly impact plant growth and development. In the current context of both global climate change and land degradation, abiotic stresses usually lead to growth restriction limiting crop production. Plants have evolved to sense and respond to maximize adaptation and survival; therefore, understanding the mechanisms involved in the different converging signalling networks become critical for improving plant tolerance. In the last few years, several studies have shown the plant responses against drought and salinity, high and low temperatures, mechanical wounding, heavy metals, hypoxia, UV radiation or ozone stresses. These threats lead the plant to coordinate a crosstalk among different pathways, highlighting the role of phytohormones and reactive oxygen and nitrogen species (RONS). Especially, plants sense these reactive species through post-translational modification (PTM) of macromolecules such as nucleic acids, proteins and fatty acids hence triggering antioxidant responses with molecular implications in the plant welfare. Here, this review compiles the state of the art about how plant systems sense and transduce this crosstalk through PTMs of biological molecules, highlighting the S-nitrosylation of protein targets. These molecular mechanisms finally impact at a physiological level facing the abiotic stressful traits that could lead to establish molecular patterns underlying stress responses and adaptation strategies.